Cytotoxicity effect of cocoa (Theobroma cacao L.) polyphenol extract on MCF-7 cells, and mode of cell death - Abdul Razak, Hazirah (2014)
The Incidence of breast cancer in Malaysia is alarming and it increased every year. It is one of the common causes of deaths among cancer patients in women. Despite of several drugs have been formulated for breast cancer treatment, these drugs can cause undesired side effects to the breast cancer patients. Therefore, scientists are searching for potential cancer chemopreventive and chemotherapeutic agents through dietary approaches. Cocoa (Theobroma cacao L.) is rich in specific antioxidants such as catechin, epicatechin and procyanidins. Previous research exhibited that cocoa possessed antioxidant and cytotoxic properties. The objective of the present study was to investigate the cytotoxicity effect of cocoa polyphenol extract (CPE) towards MCF-7 cells and its effect on mode of cell death. The phenolic constituents of CPE were evaluated by phytochemical screening, HPLC profiling and total phenolic content (TPC) assay. The antioxidant activity of CPE was determined using DPPH radical scavenging and ferric reducing antioxidant power (FRAP) assay. Cell viability was measured using MTT assay. The morphological alteration was observed using inverted light and fluorescence microscope (acridine orange/ propidium iodide dual staining). The mode of cell death was investigated using annexin V FITC-PI and DNA fragmentation assay. The apoptotic marker of cell death was carried out using p53 and caspase-9 ELISA kits. The phytochemical screening and HPLC profiling exhibited CPE contained phenolic compound particularly saponins, flavonoids and condensed tannins. TPC, DPPH IC50 and FRAP value of CPE were 13558.99±420.10 mg GAE/100g dry weight of sample, 14.73±1.47 μg/ml and 2130.33±2.33 μM FE/1 mg dry weight of sample respectively. CPE exhibited highest cytotoxicity towards MCF-7 cells with the lowest IC50 value (3 mg/ml) and exhibited significant difference (p<0.05) compared to other cancer cell lines. The difference of IC50 value was significant (p<0.05) between 24 h (4.50±0.50 mg/ml), 48 h (2.85±0.20 mg/ml) and 72 h (1.60±0.10 mg/ml). The morphological alteration of MCF-7 cells upon 48 h CPE treatment showed apoptosis and necrosis characteristics including cell membrane blebbing, cell shrinkage, nuclear condensation, apoptotic bodies and cell membrane rupture. The cell cycle analysis revealed that CPE was able to cause mild cell cycle arrest at G0/G1 phase and also induced sub-G1 peak, indicating apoptosis. Annexin V-PI assay proved that CPE induced early and late apoptosis in treated MCF-7 cells. The DNA fragmentation assay confirmed that DNA fragmentation had occurred during apoptosis in treated MCF-7 cells. The expression level of p53 and caspase-9 were increased upon CPE treatment in MCF-7 cells indicating that apoptosis was executed via mitochondria pathway. In conclusion, these findings suggested that CPE demonstrated cytotoxicity effect towards MCF-7 cells through inhibition of cell proliferation by arresting G0/G1 phase and apoptosis execution via p53 and caspase-9 activation. Based on the current findings, further research is required to develop CPE as chemopreventive agents for breast cancer.